Translation and Tourism: A Cross Cultural Communication and the Art of Translating Menus - Amirdabbaghian, Amin (Textroad Publishing Corporation, 2014)
Economic globalization has brought Iran into closer contact with the rest of the world. Iranian food, as an important part of Iranian culture, attracts foreigners who come to Iran. But in a lot of cases, when they look at to the menus, they feel stunned and baffled. For the English translations of Iranian menus are often incomprehensible and misleading. However, such awareness has not led to an in-depth study on menu translation. This paper draws on theories of foreignization and domestication, and recommends foreignization as a main strategy and domestication as a supplementary choice. Domestication strategy offers a technique that the readers of target language feel as the same as source language readers but instead, the Foreignization strategy suggests a technique that keeps source language culture inside the translated text and in another words, we can say that Foreignization strategy introduces the source language culture to the target readers. Each of the mentioned strategies has advantages and disadvantages that discussed through the present study. Through this paper, the author suggests a set of techniques for menu translation. Samples in the present study have been chosen from dish names which are translated to English. It is hoped that this will contribute to the preservation and development of Iranian cuisine culture as a whole.